2009
DOI: 10.3176/earth.2009.3.02
|View full text |Cite
|
Sign up to set email alerts
|

Biostratigraphy of the Ludlow chitinozoans from East Baltic drill cores; pp. 170–184

Abstract: The distribution of chitinozoans in the East Baltic Ludlow sequences was studied in the Ohesaare, Ventspils, Pavilosta, and Dubovskoye drill core sections. The Angochitina elongata, Eisenackitina lagenomorpha, and Eisenackitina barrandei biozones were described and correlated with the regional stratigraphical units, as well as with conodont and vertebrate biozones in the Ohesaare core.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 21 publications
0
33
0
Order By: Relevance
“…Even in the Ohesaare core, where the hiatus is of greater duration and the excursion is not recorded, strata both above and below the hiatus are still within the same chitinozoan biozone (Eisenackitina lagenomorpha Biozone), although this is much reduced in thickness by comparison with the other East Baltic cores studied by Nestor (2009). From a conodont biostratigraphical viewpoint, the level of the stratigraphical gap in the Ohesaare core is interesting: it occurs between the Paadla and Kuressaare regional stages (Jeppsson et al 1994, fig.…”
Section: Facies Changes and Unconformities Associated With The Mid Lumentioning
confidence: 85%
See 4 more Smart Citations
“…Even in the Ohesaare core, where the hiatus is of greater duration and the excursion is not recorded, strata both above and below the hiatus are still within the same chitinozoan biozone (Eisenackitina lagenomorpha Biozone), although this is much reduced in thickness by comparison with the other East Baltic cores studied by Nestor (2009). From a conodont biostratigraphical viewpoint, the level of the stratigraphical gap in the Ohesaare core is interesting: it occurs between the Paadla and Kuressaare regional stages (Jeppsson et al 1994, fig.…”
Section: Facies Changes and Unconformities Associated With The Mid Lumentioning
confidence: 85%
“…For example, Pterochitina perivelata is part of Paris's (in Kříž et al 1986) Přídolí assemblage, but has recently been found by Nestor (2009) throughout much of the Ludfordian of the Pavilosta core, Latvia. Similarly, Ancyrochitina pedavis, stated to be 'restricted to the uppermost Ludlow' by Paris (in Kříž et al 1986), occurs in both the E. lagenomorpha and E. barrandei biozones of the Pavilosta core (Nestor 2009). …”
Section: Graptolites In the Ludlow Areamentioning
confidence: 99%
See 3 more Smart Citations